The challenges faced by female expatriates in a workplace - Kilicheva Karomat; Klicheva Gavkhar (Zien Journals, 2022)
The number of expatriate women around the world has been hindering compared to males. It is also found that higher levels of stress, anxiety, and workplace discrimination, such as sexual harassment, are experienced more by women compared to men. Therefore, it is important to offer possible interventions for creating a safe and friendly working environment for workers of both genders by examining the root causes of such cases. The goal of this paper is to analyze prior studies to identify factors contributing to challenges faced by female expatriates in the workplace
Keywords: women in the workplace; gender discrimination; sexual harassment